If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-1x + -3) = 0 Reorder the terms: -4(-3 + -1x) = 0 (-3 * -4 + -1x * -4) = 0 (12 + 4x) = 0 Solving 12 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = 0 + -12 4x = 0 + -12 Combine like terms: 0 + -12 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| 7+57=q | | 2(5x+3)+11x= | | 7+57= | | 8+10x=-11x | | (7x+4)=(18x-6) | | 2(l+0.2l)=240 | | 2(18)=p | | dx=(x^2-1)*dy | | 16x=25y | | 0.16(y-9)+0.02y=0.06y-0.9 | | 16x+25y=0 | | 7w-2w= | | -3(6p+5)-2(5-17p)=3(9+5p) | | x^2-17=81 | | 5/6-x/18=1/9 | | 7b=3-2b | | 4.71=3.14a(2) | | (-5x)+3x= | | 43+34= | | 2w=40 | | 2x^2+8x+8=8 | | 3x-15=8x+7 | | 16=.25h | | -9-8(1.4H)=-17 | | -2y=3y+5 | | -12=3x+9-6x | | 25-3x=1 | | 2(l+0.4l)=364 | | 56-(3c+4)=4(c+7)+3 | | 0.07y+0.02x=5 | | 9x-12+85=0 | | -3/4r-1 |